The Influence of Work Environment, Job Stress and Workload on Employee Performance in The Ministry of Religion in South Halmahera - Berhed, Imam Tantowi; Ariani, Dorothea Wahyu (Research Horizon, 2024)
Employee performance is a very important factor in achieving work goals and cannot even be separated from an organization, whether institutional or company. The aim of this research is to test and analyze the partial and simultaneous influence of the work environment, stress and workload on employee work performance at the Office of the Ministry of Religion, South Halmahera Regency. Data collection in this research uses data collection techniques and tools in the form of questionnaires by giving a collection of written questions to respondents along with alternative answers that have been provided using the multiple linear data regression analysis method. The results of this research show that all independent variables, namely work environment, work stress and workload, partially and simultaneously have a positive and significant effect on the dependent variable, namely employee performance. Meanwhile, the results were influenced by other variables. The resulting theoretical implications support and provide evidence for previous findings, namely the successful testing of the influence of the work environment, stress and workload on employee work performance as well as providing support for previous research regarding the influence of these variables. The managerial implication is to provide input to the South Halmahera Regency Ministry of Religion Office.